2012
DOI: 10.1063/1.3693397
|View full text |Cite
|
Sign up to set email alerts
|

Quantum rod emission coupled to plasmonic lattice resonances: A collective directional source of polarized light

Abstract: We demonstrate that an array of optical antennas may render a thin layer of randomly oriented semiconductor nanocrystals into an enhanced and highly directional source of polarized light. The array sustains collective plasmonic lattice resonances which are in spectral overlap with the emission of the nanocrystals over narrow angular regions. Consequently, different photon energies of visible light are enhanced and beamed into definite directions.The development of efficient and tunable (in photon energy, direc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 20 publications
1
74
1
Order By: Relevance
“…It has been recently proposed and demonstrated that SLRs lead to an enhanced and modified emission of sources in the proximity of the array of nanoparticles [39][40][41][42]. In this section we demonstrate the modified emission of the YAG:Ce layer simultaneously coupled to quasiguided modes and SLRs.…”
Section: Photoluminescence Enhancement Measurementsmentioning
confidence: 99%
“…It has been recently proposed and demonstrated that SLRs lead to an enhanced and modified emission of sources in the proximity of the array of nanoparticles [39][40][41][42]. In this section we demonstrate the modified emission of the YAG:Ce layer simultaneously coupled to quasiguided modes and SLRs.…”
Section: Photoluminescence Enhancement Measurementsmentioning
confidence: 99%
“…With such a versatile system, the possibilities to tailor the emission from extended sources (e.g. thin layers of luminescent molecules or quantum dots) are many [20][21][22][23][24]. Previous work in this direction has focused on the interaction of SLRs with luminescent excitons in the weak coupling regime, which can even lead to photon lasing [25].…”
Section: Introductionmentioning
confidence: 99%
“…Light emission from emitters in the proximity of these systems has been recently reported. [12][13][14][15][16][17][18][19] Collective plasmonic resonances lead to the enhanced and directional emission that has been proposed for the improvement of the performance of white LEDs. [20][21][22] Here, we report on the forward emission from quasi-guided modes in polymer layers containing dye molecules.…”
mentioning
confidence: 99%